A model for the relationship between user satisfaction of healthcare facilities management and core healtcare business - Amankwah, Oti (2019)
Public hospitals in Ghana, as in many other developing countries, are faced with facilities management (FM) challenges due partly to the problem of poor services and user dissatisfaction with FM service delivery. Studies to understand the relationship between user satisfaction of healthcare FM and core healthcare business have not addressed the issue from the perspective of this study. To fill this gap, the study examined the relationship between healthcare FM services based on the FM basic framework (people - patients, place – healthcare healing environment, processes –FM service quality and technology – quality of healthcare infrastructure and equipment) and core healthcare business (healthcare personnel, healthcare delivery, adequacy of healthcare resources and healthcare administrative process). The underlying theoretical frameworks for the study included the FM basic framework, SERVQUAL theory, Core Healthcare Business dimensions and A Staff and Patient Calibration Toolkit (ASPECT) which is based on a theory of supportive designs for healthcare facilities. Questionnaire was used to gather data from 622 patients of the three surveyed hospitals (Komfo Anokye, Cape-Coast and Tamale teaching hospitals) in Ghana. The data were statistically tested and analysed by structural equation modelling (SEM) technique. Twelve of the 19 hypotheses were supported. The findings showed that although the patients are satisfied with the quality of healthcare healing environment and the quality of healthcare infrastructure and equipment, they were dissatisfied with the FM service quality. Secondly, the results indicated that healthcare FM service quality and quality of healthcare infrastructure and equipment did not have a positive significant influence on the quality of healthcare administrative process. Also, the quality of healthcare healing environment did not show a positive significant influence on healthcare delivery. The quality of healthcare infrastructure and equipment also did not have a positive significant influence on healthcare personnel. Lastly, out of the four dimensions used to evaluate the quality of core healthcare business, patients were dissatisfied with the adequacy of healthcare resources and healthcare administrative process. Generally, the study model offered a good understanding of the factors that influenced the relationship between users (patients) satisfaction of healthcare FM and core healthcare business. The findings indicated that healthcare institutions must realize that quality healthcare FM service is a means for the healthcare organisations to stay relevant in the eyes of the patients. Thus, the study recommends that the surveyed teaching hospitals in Ghana should aim to achieve patient centered healthcare service deliver by effectively improving the quality of both their FM and core healthcare services, since patient satisfaction leads to patient loyalty.